Peran Wanita dalam Pemanfaatan Pangan pada Rumah Tangga di Desa Dunggala Kecamatan Tapa Kabupaten Bone Bolango - Eyato, Fadila; Bakari, Yuliana; Singgili, Haris (Universitas Galuh, 2026)
Food utilization is the process of using food ingredients to meet household nutritional and energy needs. This study aims to analyze the influence of the role of female farmers on food utilization in households in Dunggala Village, Tapa District, Bone Bolango Regency. The study used a survey method on 55 female farmers who were selected purposively. Data were collected through interviews and documentation, then analyzed descriptively and quantitatively using multiple linear regression. The results showed that the role of female farmers in food consumption had a significant negative effect on food utilization, while their role in food processing, food production, and food storage techniques had a significant positive effect. The coefficient of determination (R²) was 0.825, meaning 8.25% of the variation in food utilization was explained by these four roles. This finding underscores the need to increase the capacity of female farmers, particularly in the processing and consumption of healthy and diverse foods, to strengthen household food security.